Study of efficiency technique (energy management) in application to the Korean Language Centre building at the ITM campus, Shah Alam, Selangor / Mohamed Nor Badiazaman - Badiazaman, Mohamed Nor (1997)
Rapid development requires efficient energy usage. New devices and products have been designed and produced for lighting and air-conditioning efficiency by world wide manufacturers. This report summarises the result of an energy efficiency study performed for the Korean Language Centre building at the Mara Institute of Technology campus in Shah Alam, Selangor.